Diversity of Cropping Patterns and Land Use Practices in Faridpur Region - Mostafizur, ABM; Zaman, MAU; Shahidullah, M; Nasim, M (Bangladesh Rice Journal, 2018)
The development of agriculture sector largely depends on the reliable and comprehensive statistics of the existing cropping patterns, cropping intensity and crop diversity of a particular area, which will provide guideline to policy makers, researchers, extensionists and development workers. The study was conducted over all 29 upazilas of Faridpur region during 2015-16 using pre-tested semi-structured questionnaire with a view to document the existing cropping patterns, cropping intensity and crop diversity of this area. From the present study it was observed that about 43.23% net cropped area (NCA) was covered by only jute based cropping patterns on the other hand deep water ecosystem occupied about 36.72% of the regional NCA. The most dominant cropping pattern Boro−Fallow− Fallow occupied about 24.40% of NCA with its distribution over 28 out of 29. The second largest area, 6.94% of NCA, was covered by Boro-B. Aman cropping pattern, which was spread out over 23 upazilas. In total 141 cropping patterns were identified under this investigation. The highest number of cropping patterns was identified 44 in Faridpur sadar and the lowest was 12 in Kashiani of Gopalganj and Pangsa of Rajbari. The lowest crop diversity index (CDI) was reported 0.448 in Kotalipara followed by 0.606 in Tungipara of Gopalganj. The highest value of CDI was observed 0.981 in Faridpur sadar followed by 0.977 in Madhukhali of Faridpur. The range of cropping intensity value was recorded 113- 262%. The maximum value was for Saltha of Faridpur and minimum for Kotalipara of Gopalganj. As a whole the CDI of Faridpur region was calculated 0.971 and the average cropping intensity at regional level was 197%. Bangladesh Rice j. 2017, 21(2): 157-172